Normative state power in international relations - Koivisto, Marjo (Oxford : Oxford University Press, 2012)
A theory of the role of scientific and moral cultures in state transformations in 20th century global politics. Breaking down methodological nationalism, and basing its case study findings in historical analysis, it encompasses international relations politics, and political sociology.
Includes bibliographical references and index.
Description based on print version record.
Keywords: International relations -- Philosophy; International relations -- History -- 20th century